Pengembangan Media Pembelajaran Spinning Wheel of Question pada T Ema 7 Subtema 2 Kelas V di MIN 1 Medan T.A. 2022/2023 - Elsa Febrina Harahap; Laurensia Masri Perangin-Angin; Nurmayani Nurmayani; Risma Sitohang; Elvi Mailani (Departement of Mathematics Education, 2024)
This research was conducted due to the lack of use of various learning media at MIN 1 ME and made learning monotonous, students were less enthusiastic and active in participating in learning so that student learning outcomes were low. The purpose of this research is to produce learning media for spinning wheel of questions that are valid, practical, and effective. The type of research used in this study is the 4-D Thiagarajan R&D (Research and Development) model. The test subjects consisted of material experts, media experts, teachers and 29 fifth grade students of Medina 3. Data collection techniques in this study were observation, interviews, questionnaires, tests and documentation. Data analysis techniques in this study are descriptive qualitative and quantitative descriptive analysis techniques. The results of the development of the spinning wheel of question media showed that the material validation was very valid in the second stage of validation (90%) and the results of the media validation were stated to be very valid in the first stage validation (91.6%), the validation of educational practitioners' experts was stated to be very practical (92%). As for the results of the effectiveness test based on the results of the pre-test and post-test scores using the N-Gain formula, a value with a percentage of 73% is obtained and is categorized as